1998
DOI: 10.1093/jn/128.11.2014
|View full text |Cite
|
Sign up to set email alerts
|

Low Nutritional Quality of Unconventional Tropical Crop Seeds in Rats

Abstract: As the search for alternative sources of food to alleviate hunger continues, this study was undertaken to determine the biological value in growing rats (BV) of proteins of some lesser known tropical seeds gathered in Nigeria. Antinutritional factors (trypsin inhibitors, phytic acid, oxalate, tannin, alkaloids) and amino acid compositions were also determined, and protein digestibility-corrected amino acid score (PDCAAS) was calculated using the amino acid requirement pattern of the preschool child and individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
3
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 41 publications
9
46
3
4
Order By: Relevance
“…In a study by Ortega (1996) on P. juliflora, methionine concentration was higher than that measured in the present study for P. laevigata. The methionine concentration for P. laevigata in the present study was similar to concentrations in P. Africana, as reported by Proll et al (1998) and Yusuf et al (2008). In C. siliqua the lysine concentration found in this study was lower than Dakia et al (2007) reported.…”
Section: Resultssupporting
confidence: 88%
“…In a study by Ortega (1996) on P. juliflora, methionine concentration was higher than that measured in the present study for P. laevigata. The methionine concentration for P. laevigata in the present study was similar to concentrations in P. Africana, as reported by Proll et al (1998) and Yusuf et al (2008). In C. siliqua the lysine concentration found in this study was lower than Dakia et al (2007) reported.…”
Section: Resultssupporting
confidence: 88%
“…These ANFs have been suggested as probable factor that militated against the digestibility of crude protein (CP) and amino acids (AAs) in most plant products. Phytic acid levels in the TDLMs were high and similar to those earlier reported (Proll et al, 1998). When ingested by non-ruminants, phytic acid can bind with proteins to form phytate protein complexes (Saio et al, 1967).…”
Section: Proximate Composition and Phytochemical Screening Of Tdlmsupporting
confidence: 84%
“…Measurements were performed 2 weeks before implantation (background measurement) as well as 2 and 12 weeks after implantation. During indirect calorimetry, urine was collected daily for determination of nitrogen excretion using a Kjeldahl method (Proll et al, 1998). Gas analysis was performed using the analyzing system Advanced Optima (Hartmann & Braun GmbH & Co. KG, Frankfurt/Main, Germany) containing an oxygen (Magnos 16) and a carbon dioxide (Uras 14) analyzer.…”
Section: Measurementsmentioning
confidence: 99%